ALTURA DAS EDIFICAÇÕES E SUAS INTERFACES TÉRREAS: UMA AVALIAÇÃO DE SEUS IMPACTOS ESTÉTICOS AO NÍVEL DA RUA - Antocheviz, Fabiana; Reis, Antônio Tarcísio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper aims is to evaluate the aesthetic impact at ground floor level of buildings different heights and distinct ground floor interfaces in the Coastal City of Capão da Canoa, by architects and non-architects college graduated. The city has experienced a growing urban expansion, characterized by significant morphological transformations, among which stands out the reduction of physical and visual permeability between of buildings ground floor interfaces and the increase of buildings height. Data were collected through questionnaires accessible via internet to the following two groups of respondents: 47 architects and 91 nonarchitects college graduated. Scenes representing different urban contexts of the city, shaped according to different Master Plans, and characterized by buildings with different heights and ground floor interfaces were part of the questionnaires. Data analysis was performed trough non-parametric statistical tests, namely Kendall's W and Mann-Whitney. The results indicate, for example, that, regardless the type of formal education of the respondents, the higher the height of the buildings, the less preferred is the scene.